Error Solving PISA-Oriented Math Problem Content Quantity Junior High School Students - Budi Murtiyasa; Asiyah Asiyah (AL-ISHLAH: Jurnal Pendidikan, 2022)
The low mathematical literacy of students causes students to find it challenging to solve PISA-type questions, so they make mistakes. This study examines errors in solving PISA-oriented mathematical problems based on Newman's error analysis. This research involved 14 subjects of class VII A Junior High School Batik Special Program Surakarta. This research data results from error data analyzed from students' answers to solve PISA math problems. Data collection techniques used are written tests, interviews, and documentation. This research instrument uses three items of mathematical problems described from PISA in 2012 on quantity content. After the questions are ready, the next step is consulting the instrument with the supervisor. Before being tested, the questions went through a validation process by one lecturer and one mathematics teacher. The validity of the data in this study uses triangulation techniques. Data analysis techniques are data reduction, data presentation, and conclusions. Based on the results of writing tests and interviews obtained that 1) comprehension errors with a percentage of 23.68% of the cause because students do not understand the meaning of the question, 2) transformation errors with a percentage of 13.16% of the cause due to students confused filtering information and using relevant mathematical procedures, 3) errors of process skills with a percentage of 23.68% of the cause due to lack of skilled running the calculation operation, 4) writing errors of final answers with a percentage of 39.48% The reason is that students are not used to writing conclusions on the answer sheet.